2022
DOI: 10.1093/jamia/ocac066
|View full text |Cite
|
Sign up to set email alerts
|

Automated medical literature screening using artificial intelligence: a systematic review and meta-analysis

Abstract: Objective We aim to investigate the application and accuracy of artificial intelligence (AI) methods for automated medical literature screening for systematic reviews. Materials and Methods We systematically searched PubMed, Embase, and IEEE Xplore Digital Library to identify potentially relevant studies. We included studies in automated literature screening that reported study question, source of dataset, and developed algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…In addition, both methods performed well in the binary classification of records, but not as much for providing the reasons for exclusion using the pre-specified PICOS criteria. In a recent meta-analyses of AI algorithms for automated searches, the combined recall, specificity, and precision values were 0.928 [95% confidence interval (CI), 0.878– 0.958], 0.647 (95% CI, 0.442–0.809), and 0.200(95% CI, 0.135–0.287) when achieving maximized recall, and were 0.708 (95% CI, 0.570–0.816), 0.921 (95% CI, 0.824–0.967), and 0.461 (95% CI, 0.375–0.549) when achieving maximized precision [19]. The approach used in the present study was not designed to optimize either recall or precision; however, the values of recall (0.78 to 0.86), specificity (0.85 to 0.90), and precision (0.33 to 0.74) obtained with the binary classification of records in the present study are within the range of values reported by Feng et al [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, both methods performed well in the binary classification of records, but not as much for providing the reasons for exclusion using the pre-specified PICOS criteria. In a recent meta-analyses of AI algorithms for automated searches, the combined recall, specificity, and precision values were 0.928 [95% confidence interval (CI), 0.878– 0.958], 0.647 (95% CI, 0.442–0.809), and 0.200(95% CI, 0.135–0.287) when achieving maximized recall, and were 0.708 (95% CI, 0.570–0.816), 0.921 (95% CI, 0.824–0.967), and 0.461 (95% CI, 0.375–0.549) when achieving maximized precision [19]. The approach used in the present study was not designed to optimize either recall or precision; however, the values of recall (0.78 to 0.86), specificity (0.85 to 0.90), and precision (0.33 to 0.74) obtained with the binary classification of records in the present study are within the range of values reported by Feng et al [19].…”
Section: Discussionmentioning
confidence: 99%
“…SVM was considered separately because evidence suggested that SVM classifiers had the best performance for text classification [19]. There were no significant differences in recall, specificity, and precision between SVM and other algorithms collectively [19]. In the present study, fine-tuned BERTs and SVMs were applied to the title and abstract screening phase of two separate clinical SLRs and the results compared with those obtained by humans.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the large number of available tools and evaluations of their accuracy, little has been published to bring together these evaluations and nothing to compare the accuracy of tools. An extensive systematic review [31] synthesized tool accuracy across studies but made no attempt to compare the accuracy of different tools. This type of comparative assessment is currently limited by the heterogeneity of methods used in different studies.…”
Section: Machine Learning Screening Tools For Systematic Reviewsmentioning
confidence: 99%